Prospective and territorial development in island areas: Empirical evidence from Bocachica-Colombia (2019)
The objective of this article is the construction of future stages in the framework of territorial development for the Island of Bocachica in Colombia through collective construction among state community and participating researchers that was intended to provide the territory inputs for reflection on the future of the Island, from its historical vocation and economic development of the island. Three methods were used: structural analysis, analysis of actors, and construction of stages. The first allowed to identify the key factors in the political, economic, social, and environmental dimensions, highlighting those key variables that dynamize the transformations in the system; secondly, the analysis of actors, which contributed to determining the relations between the key actors of the territory and their degree of power, as well as their convergences and divergences with respect to the key variables identified in the structural analysis. Finally, the construction of stages made it possible to identify three future scenarios with high probability of occurrence. The most important findings of the research show that, if the trend continues in the Island with respect to its territorial development, it is more likely that the economic and social problems it currently presents will continue.